Epidemiologic associations of HPV‐positive oropharyngeal cancer and (pre)cancerous cervical lesions. Issue 2 (2nd March 2018) - Rietbergen, M.M.; van Bokhoven, A.A.J.D.; Lissenberg‐Witte, B.I.; Heideman, D.A.M.; Leemans, C.R.; Brakenhoff, R.H.; Bloemena, E.
Abstract : Human papillomavirus (HPV)‐induced oropharyngeal squamous cell carcinoma (OPSCC) remains increasing worldwide. We aimed to investigate if the HPV‐prevalence of OPSCC in the Netherlands is rising as well, also in female patients. In addition, we evaluated the association between HPV‐positive OPSCC and suspicious Pap results of the cervix in these female patients. Patients with OPSCC treated in the period 2000–2015 at the VU University Medical Center Amsterdam, were included ( n  = 926). The presence of an oncogenic HPV infection was determined by p16‐immunostaining, followed by a high‐risk HPV general primer 5+/6+ DNA PCR on the p16‐immunopositive cases. A review of pathology reports in all female patients ( n  = 305) was undertaken to identify cytological signs of HPV‐related (pre)cancer of the cervix. In total 281 of 926 (30.3%) OPSCCs were HPV‐positive. Moreover, a significant increase in the prevalence of HPV‐positive OPSCCs was observed from 14.0% in 2000 to 48.1% in 2015 ( p  < 0.001). Among the female patients with an HPV‐positive OPSSC ( n  = 70), the results of cervical smears were available in 56 of 70 patients (80.0%). Of the female patients with HPV‐positive OPSCC, 9 of 56 (16.1%) patients had a vaginal cuff Papanicolaou (Pap) test ≥3b in their medical history compared to 7 of 168 (4.2%) in the HPV‐negative group ( p  = 0.003). In conclusion, a continuous increase in the HPV‐attributable fraction of OPSCC was demonstrated in the period 2000–2015 in the Amsterdam region. HPV‐positive OPSCC has a significant association with a history of suspicious Pap results of the cervix in female patients. Abstract : What's new? Human papilloma virus (HPV) is best known as the causative agent for cervical cancer but also induces other cancers including oropharyngeal squamous cell carcinoma (OPSCC). Here the authors demonstrate an increase in the HPV‐attributable fraction of OPSCC in the Netherlands, both for men and women. In women, an association was found between HPV‐positive OPSCC and cytological signs of precancerous lesions of the cervix. These findings might inform screening programs for OPSCC in the near future.